3D Kinematics of Male and Female Soccer Players for a Variety of Game-Specific Skills - Danyon Loud; Paul Grimshaw; Richard Kelso (Applied Bionics and Biomechanics)
Soccer is played by a variety of individuals with varying abilities. The complicated lower limb movements involved within the game often lead to knee and ankle injuries, with anterior cruciate ligament injuries being the most severe with regard to rehabilitation time and ongoing health risks. This research explores the biomechanical kinematics of male and female soccer players on synthetic grass to determine whether trends in lower limb biomechanics over a variety of movements could explain injury risk. Both male and female players (n = 10) aged between 19 and 24 years performed running-based and stationary-start movements. Biomechanical measurements at the hip, knee, and ankle were recorded. Observations showed that specific differences in joint angles were largely dependent on the movements performed; however, for male players, on average, across all movements, 84.6% and 72.6% of the variation in joint angles could be explained by internal/external rotation at the hip and knee, respectively. For female players, internal/external knee rotation, as well as hip abduction and adduction, accounted for 83.6% and 80.2% of the variation in joint angles, respectively, across all the tested movements. This highlights the importance of hip mechanics and knee alignment for players when performing a variety of movements.